AGROCHEMICAL PROPERTIES OF IRRIGATED SOILS - Boboev Farrukh Farkhodovich (Modern American Journals, 2025)
Today, in the development of agriculture in our republic, increasing soil fertility is of particular importance, depending on its condition, the cultivation of agricultural land, and the use of agrotechnical measures. Scientific research is being conducted worldwide in a number of priority areas related to the state of soil fertility, its indicators, the relationship between soil fertility and other factors, and soil fertility modeling. In addition, modern geoinformation technologies are used to study soil properties, assess, improve soil fertility, and manage it, and relevant developments are being introduced into production.
Keywords: Structure, agrochemical index, soil-climatic, mechanical composition, humus, saline soils, organic matter, agrotechnical measure, salinity, soil environment, amount of NPK.